Síndrome metabólica e risco cardiovascular na pós- menopausa: avaliação por diferentes critérios diagnósticos e influência de fatores sócio-econômicos - Silveira, Inavan Lopes da (2008)
The metabolic syndrome (MetS) involves a group of risk factors and is associated with a significantly higher risk of developing cardiovascular diseases (CVD) and type 2 diabetes. Recent studies have shown the importance of preventing CVD through early diagnosis and treatment of patients with MetS. The objective of our study was to determine the prevalence of MetS by different diagnostic criteria in postmenopausal women and analyze the influence of socioeconomic factors on cardiovascular risk in this sample of the population. A cross-sectional study involving 127 postmenopausal women (45 to 64 years) from Natal and Mossoró, Brazil. The study was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte. The experimental protocol consisted of applying structured interview, clinical examination and implementation of dosages blood. The diagnosis of MetS was based on NCEP-ATP III (National Cholesterol Education Program-Adult Treatment Panel III) and IDF (International Diabetes Federation) criteria. The research was accomplished with the participation of an interdisciplinary team in their several phases. The result of the sample studied had mean age of 53.9 ± 4.6 years and per capita income of 54.5 dollars. The prevalence of MetS, according to NCEP-ATP III and IDF criteria, was 52.8% and 61.4$, respectively. The agreement rate between NCEP-ATP III and IDF criteria was 81.9%, with a kappa value of 0.63 (CI 95%, 0.49-0.76), indicating good agreement between the two definitions. The most prevalent cardiovascular risk factor was HDL < 50 mg/dl, observed in 96.1% of the women analyzed, followed by increased waist circumference (≥ 80 cm) in 78.0%, elevated blood pressure in 51.2%, triglycerides ≥ 150 mg/dl in 40.9% and glycemia ≥ 100 mg/dl in 37.0% of the women. The occurrence of MetS was significantly associated with schooling and body mass index (BMI). High blood pressure was significantly associated with low family income, low schooling and weight gain. There was no significant association between the intensity of climacteric symptomatology and the occurrence of MetS. The conclusions of the research were that MetS and its individual components show a high prevalence in postmenopausal Brazilian women, and significant associations with weight gain and low socioeconomic indicators. The data point to the need for an interdisciplinary approach at the basic health care level, directed toward the early identification of risk factors and the promotion of cardiovascular health of climacteric women.